2021
DOI: 10.3390/cancers13143484
|View full text |Cite
|
Sign up to set email alerts
|

Light Technology for Efficient and Effective Photodynamic Therapy: A Critical Review

Abstract: Photodynamic therapy (PDT) is a cancer treatment with strong potential over well-established standard therapies in certain cases. Non-ionising radiation, localisation, possible repeated treatments, and stimulation of immunological response are some of the main beneficial features of PDT. Despite the great potential, its application remains challenging. Limited light penetration depth, non-ideal photosensitisers, complex dosimetry, and complicated implementations in the clinic are some limiting factors hinderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 243 publications
0
85
0
Order By: Relevance
“…To our knowledge, there is no dedicated review of implants for PDT. A section devoted to the description and critical review of selected implants can be found in a recent review of light technology for PDT [230].…”
Section: Dosimetry and Sourcesmentioning
confidence: 99%
“…To our knowledge, there is no dedicated review of implants for PDT. A section devoted to the description and critical review of selected implants can be found in a recent review of light technology for PDT [230].…”
Section: Dosimetry and Sourcesmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is defined as phototherapy of abnormal cells using photosensitizers and light sources. Since PDT is composed of light, photosensitizers and oxygen species are believed to be the safe candidates for cancer treatment [ 16 , 17 , 18 ]. PDT using photosensitizers does not significantly affect the viability of surrounding normal cells or tissues in the absence of light because photosensitizers are only activated in the irradiation field, producing ROS and thus killing the abnormal cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since PDT is composed of light, photosensitizers and oxygen species are believed to be the safe candidates for cancer treatment [ 16 , 17 , 18 ]. PDT using photosensitizers does not significantly affect the viability of surrounding normal cells or tissues in the absence of light because photosensitizers are only activated in the irradiation field, producing ROS and thus killing the abnormal cells [ 16 , 17 , 18 ]. Furthermore, PDT would be an adequate option for squamous phenotype of tumor because the irradiation depth of tissues is less than 15 mm [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PDT, typically one uses visible light, which is able to penetrate tissues in the so-called therapeutic window to centimeters of depth [ 15 ], thereby reaching shallow tumors only. In order to overcome this limitation and target deeper tumors, other light sources have been tested [ 16 ]. Among them, electromagnetic radiation such as near infrared light [ 16 , 17 , 18 ], Cherenkov radiation [ 19 , 20 , 21 ], and X-rays [ 22 , 23 , 24 , 25 ] have been used.…”
Section: Introductionmentioning
confidence: 99%